The REACH directive and its impact on the European chemical industry: a critical review - Lorenz, Tobias; Lebreton, Baptiste; Van Wassenhove, Luk N. (Fontainebleau, 2008)
"The REACH Directive, requiring the registration and testing of more than 30,000 existing chemical substances prior to selling them in the European Union, has been very controversial from its initial draft in 2001 to its adoption in 2006. In the course of lobbying actions, various studies have been published to assess the implementation costs of REACH, but cost estimations range from $ 500 million to $ 150 billion. A recent survey by INSEAD shows that the chemical industry is still very pessimistic about the long-term impact of REACH on the competitiveness of the European manufacturing base. The objective of this article is to explore to what extent REACH will impact Europe's chemical manufacturing sector. For this purpose, we present the main characteristics of the legislation in a first section. We then review the impact assessment studies published in section two. Based on these studies, we investigate whether REACH could impact future product innovation as well as hurt Europe's cost competitiveness on global markets in section three. We conclude that the impact will most probably be minor but that more empirical evidence is required."